Malangali and the Cyberians: refelctions on the Internet living Swahili dictionary. - Benjamin, Martin (Africa Today)
The writer draws on his often conflicting experiences as general editor of the Kamusi Project's Internet Living Swahili Dictionary and as a field researcher in economic anthropology in Malangali, Tanzania, to discuss Africa and the “Information Age.” He describes the Kamusi Project, which developed out of dissatisfaction with current reference materials for Swahili-speaking students of English and English-speaking students of Swahili, outlining how the project decided to produce a dictionary by pulling together a diverse group of Swahili speakers and scholars to create a database that could be refined over time. He states his concern about the introduction of the Internet to Malangali, because Malangali does not suffer from the lack of community that draws other societies to the Internet. He is also anxious about the economic effects of the Internet, asserting that there is every reason to believe that people in Malangali will get the raw end of the deal in any encounter with international corporate culture. However, he concludes that the benefits of having computers technology in East Africa appear to outweigh the dangers.